Imperceptibility Analysis for Watermarking Technique Based on Image Block Division Scheme - Abdullad, Maryam Jasim; Ismail, Amelia Ritahani; Abubakar, Adamu (IEEE Explore, 2021)
Image watermarking techniques proposed different algorithm schemes to improve performance quality. For a medical image, the watermarking techniques are required to give significant attention to achieve the highest imperceptibility performance to remain visual quality. That is why this paper analyzes two different watermarking algorithm schemes: image block division 88 and image block division 22 to determine the imperceptibility performance for each. Both schemes used the fitness evaluation to evaluate the imperceptibility performance of each embedding location. Thereafter, the imperceptibility, embedding capacity, and watermark data bit error of both schemes were measured. The experiment results show that the image block division 88 scheme outperformed in imperceptibility performance under Peak Signal-to-Noise Ratio (PSNR) values for the three different watermarked medical images is 106.1014 to110.5222. The image block division 22 scheme outperformed in embedding capacity and watermark data bit error where the embedding capacity is 1449 to 31953 bit and watermark data bit error is zero for the three different watermarked medical images. This finding indicates that the watermarking technique with image block division 22 scheme can achieve more accurate performance.